Results of meniscectomy for treatment of isolated meniscal injuries: Correlation between results and etiology of injury - Camanho, Gilberto Luis (2006)
PURPOSE: To evaluate the results of the treatment of patients with isolated meniscal injuries of different etiologies. MATERIALS AND METHODS: 435 patients of both sexes and different age groups underwent meniscectomy after their isolated meniscal injuries were clinically diagnosed and confirmed by nuclear magnetic resonance imaging. RESULTS: Most patients achieved good results and were able to return to the activities they had practiced prior to surgery without major limitations. CONCLUSIONS: Meniscectomy for the treatment of traumatic meniscal injury provides better results than meniscectomy for the treatment of degenerative meniscal injury. The results of meniscectomy for the treatment of meniscal injury due to fatigue are similar to those of meniscectomy for the treatment of traumatic meniscal injury, although the risk of osteonecrosis development is higher.